The Comprehensive Assessment and Enhancement of Team Effectiveness - Kumari, Sarita
When a gifted team dedicates itself to unselfish trust and combines instinct with boldness and effort, it is ready to climb Patanjali, The Mahabhasya, 2nd c. BCE Much of the organizations work is accomplished directly or indirectly through various teams. Team has a higher commitment to common goals of the organization. It has a clear purpose, clear roles and work assignments. Team facilitates open and free communication among the members leading to effective result. The purpose of this research is to study and analyze how to assess and enhance the effectiveness of a team so that it motivates the team members, helps in improved morale, accountability and commitment, and effective time management which in turn take the organization to a new height. The research design adopted for this study is exploratory in nature. Hypotheses are formulated and proved. The primary data are collected through the distribution of structured questionnaires to the employees. Assessment and enhancement of team effectiveness is very essential for the organizations. This in turn helps in driving the business for excellence.
Keywords: Goal; Leadership; Openness; Team Effectiveness; Excellence; Trust